Aggressive Epstein‐Barr virus‐negative B‐cell post‐transplant lymphoproliferative disorder in a hepatitis C‐negative liver transplant recipient who received a hepatitis C‐positive graft: Implications for D+/R− hepatitis C virus seroconversion. Issue 5 (22nd July 2019) - Kutzler, Heather L.; Collins, Katrina; Maneckshana, Bejon; Rochon, Caroline; Einstein, Michael; Mnayer, Laila; Rezuke, William N.; Sheiner, Patricia; Serrano, Oscar K.
Abstract: Post‐transplant lymphoproliferative disorder (PTLD) is an uncommon, but well‐described complication after liver transplantation. Most recently, Hepatitis C virus (HCV) has been implicated in the development of PTLD. A HCV‐negative 62‐year‐old man with autoimmune hepatitis received a HCV nucleic acid amplification test‐positive liver graft from a 73‐year‐old brain‐dead donor (D+/R−). After his recovery from the operation, the patient was treated for HCV and achieved an undetectable viral load. He was readmitted 6 months after transplant with a spontaneous perisplenic hematoma, weight loss, failure to thrive, low‐grade fevers, and abnormal liver function tests. He had a rapid clinical deterioration and expired shortly after admission. His liver biopsy demonstrated EBV‐negative monomorphic B‐cell PTLD. Our case is the first to report an aggressive early‐onset EBV‐negative monomorphic B‐cell PTLD in a HCV D+/R− liver transplant. This case illustrates the paucity of knowledge on HCV seroconversion and its involvement in EBV‐negative monomorphic B‐cell PTLD development.